THE INFLUENCE OF READING INTEREST ON ACHIEVEMENT MOTIVATION OF ENGLISH LITERATURE STUDENTS OF BINA DARMA UNIVERSITY IN PALEMBANG - Fitria Aprilia; Ninuk Lustyantie; Zainal Rafli (State Islamic University of North Sumatra Indonesia, 2020)
Reading interest becomes one of the most substantial issue in the latest research nowadays. This research aims to investigate the influence of reading interest on students’ achievement motivation of the undergraduate students of English Literature Study Program of Bina Darma University in Palembang. To achieve the aim, the questionnaires of reading interest and achievement motivation were administered to a group of 60 students who became the sample of the study. The questionnaires before had been piloted to other students out of the sample in order to check the validity and reliability. To analyze the data, path analysis was used and the result showed that there was a positive direct effect of reading interest on English literature students’ achievement motivation with the coefficient value 0.449. In addition, the magnitude of the direct effects of reading interest on students’ achievement motivation was 20.2%. Finally, the interpretation, implications and recommendation of the results were also discussed. Keywords: Reading Interest, Achievement Motivation, English Literature Students